Proceedings of the 24th ACM SIGKDD International Conference on Knowledge Discovery &Amp; Data Mining 2018
DOI: 10.1145/3219819.3219912
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Paroxysmal Atrial Fibrillation using Attention-based Bidirectional Recurrent Neural Networks

Abstract: Detection of atrial fibrillation (AF), a type of cardiac arrhythmia, is difficult since many cases of AF are usually clinically silent and undiagnosed. In particular paroxysmal AF is a form of AF that occurs occasionally, and has a higher probability of being undetected. In this work, we present an attention based deep learning framework for detection of paroxysmal AF episodes from a sequence of windows. Time-frequency representation of 30 seconds recording windows, over a 10 minute data segment, are fed seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 46 publications
0
57
0
Order By: Relevance
“…Indeed, we have shown that detecting PAC/PVC can lead to significant false positive reduction during AF detection [ 40 ]. Other recent published reports [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] have largely focused on AF without accounting for PAC/PVC and consequently their accuracy of AF detection was suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have shown that detecting PAC/PVC can lead to significant false positive reduction during AF detection [ 40 ]. Other recent published reports [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] have largely focused on AF without accounting for PAC/PVC and consequently their accuracy of AF detection was suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…2). [32][33][34] Traditionally, prominent features were derived from the tachogram (RR intervals) since it is a reliable measure of heart beats. 35 Realizing that PPG waveforms may carry physiological information beyond heart rate, new features beyond RR intervals were derived.…”
Section: Ppg-based Af Detectionmentioning
confidence: 99%
“…raw plot of the signal, fast Fourier transform spectrum, or wavelet spectrogram-represented in the Fig. 2 in PPG representation part) were used with promising results in the detection of physiological events, 32,37,38 Images for PPG representation in Fig. 2 is a general depiction of the format types of information used by the different algorithms.…”
Section: Ppg-based Af Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the field of AI, DNN has also been utilized in diverse scientific disciplines, including the fields of biomedicine (Liang et al, 2018;Shashikumar et al, 2018), economics (Singh & Srivastava, 2017;Yong et al, 2017), chemistry (Fooshee et al, 2018;Sun et al, 2019), and physics (Bhimji et al, 2018;Sadowski & Baldi, 2018). Despite the numerous successes obtained with DNN, limitations remain concerning the application of DNN in numerous scientific problems due to the following reasons: First, a large amount of data is usually requisite to guarantee model accuracy.…”
Section: Introductionmentioning
confidence: 99%